(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
This article shows an analysis of the reform strategies for the State and public administration in Latin American countries raised by neoliberalism in the 1990s, the doctrines of New Public Management (NPM) formulated in the context of the reform to improve the performance of public administration and the relationship between administrative doctrines and politics. The analysis is based on three guiding questions: 1. What is the context of the reforms to the State and public administration proposed by neoliberalism at the end of the 20th century? 2. What are the characteristics of the reforms proposed by the New Public Management to redesign public administration? and, 3. How were the reforms and the new public management articulated with the clientelism and patrimonialism characteristic of the political system? The proposed thesis is that the reform of the State and public administration focused on the economic dimension rather than the administrative institutions and ended up becoming instruments for strengthening the electoral power of the Colombian ruling elite, to the detriment of public function, labor decent and labor rights. The methodology is descriptive and analytical, using the documentary review to put authors into dialogue, propose relationships between conceptual categories and present some perceptions and analyzes of the authors as a result of their consulting-type investigative experience.